Design and implementation of high speed modem for VHF and UHF band [electronic resource] - 279374 Chua, Tiong Chong (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 200